The Introduction of Information and Communication Technology in the Framework of Preschool Education - Cireasa, Ioana-Theodora (Technium Education and Humanities, 2023)
The Romanian education system has had to adapt to the new challenges brought on by the pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Thus, it is expected of preschool teachers to integrate and use Information and Communications Technology (ICT) in their teaching approach. The purpose of this study is to explore the preschool teachers' perception on quality usage of ICT. Based on qualitative data, we have started with the question; "What is the preschool teachers' perception regarding the possibilities and the limits that come with the introduction of ICT in the preschool curriculum?" The pattern was determined by using the sampling criteria which is an intentional sampling method. This was used to select 25 preschool teachers (N=25) from state kindergartens. The data were collected through semi-structured interviews that lasted up to one hour and were based on the semi-structured interview guide. The interviews were recorded, recorded and transcribed, in order to make the main textual analysis, which was based on a thematic analysis, thus identifying three main themes. Our results show that there is a need for change, where teachersʼ technological pedagogical knowledge needs improvement, in terms of how they are supposed to integrate technology for childrenʼs invovment in the teaching-learning process. Furthermore, the preschool teachers have emphasized on their expectations in being supported through the creation of a school curriculum and more programs that involve improving their abilities in using technology. Preschool teachers are aware not only of the advantages of technology, but also of the possible disadvantages.